Thesis Title Eligibility Decision Support System using the Simple Additive Weighting Method at STMIK Palcomtech - Riki Maryono Apriando; Lepian Mardinata; Barita Ardianto (Journal of Intelligent Decision Support System (IDSS), 2021)
Decision Support System (DSS) is a system that can assist a person in making accurate and targeted decisions. Many problems can be solved using SPK, one of which is the feasibility of the thesis title at STMIK PalComTech Palembang. There are several methods that can be used in building a DSS including Simple Additive Weighting (SAW). As in the SPK the eligibility of the thesis title. This study uses the SAW method in determining the feasibility of the thesis title at STMIK PalComTech Palembang. In determining the feasibility of the thesis title, there are several criteria that become the basis for making decisions, including Journal, unique title, 5W 1H (What, Where, When, Why, Who and How)(Fitriani & Alasi, 2020). Journal means whether the student fulfills all the journals to meet the eligibility requirements for the thesis title. A unique title means that students must be able to submit a title that has never existed or an existing title is then redeveloped so that it is not the same as the previous title. 5W 1H is the title eligibility criteria that must be met. And in the development of the model using a prototype. The final result in this research is to get an assessment that is ordered from the lowest to the highest, so that the supervisor and the Head of Study Program can easily make decisions by looking at the results of the SPK.